Językowa tożsamość uczestników komunikacji internetowej. Na przykładzie grupy dyskusyjnej - Płowens, Jakub (Investigationes Linguisticae, 2008)
This article describes language communication of the Internet discussion group. Linguistic material derives from the fans’ discussion group dedicated to one of the most famous Bulgarian rock bands called Б.Т.Р. (B. T. R.). In order to present language behaviours and subsequent relationships between users, interdisciplinary methods were applied in an analysis of the group’s language. The objective of this article is to find the social character that reveals itself in the language (linguistic identity) of the users’ environment. The article proves the existence of the value-system that enables an attribution of the organisational culture’s features into the community of the discussion group users.